ISTRAŽIVANJE INTERNIH INDIKATORA FINANSIJSKE STABILNOSTI OSIGURAVAJUĆIH DRUŠTAVA U REPUBLICI SRBIJI - Stevanović, Tatjana; Stanković, Jelena; Stanković, Jovica (International Journal of Economic Practice and Policy, 2021)
Dynamic changes in the insurance sector require a new system of performance measures, which enables monitoring of multiple business segments of insurance companies and meets the information requirements of a large number of different stakeholders. In this regard, in the Republic of Serbia a multidimensional system of performance measures is used - the CARMEL framework, made according to the methodology of the International Monetary Fund. Due to the fact that these indicators indicate the effectiveness of different business segments, the analysis of the performance of insurance companies cannot be based only on one of these groups. Assessment of financial stability and ranking of insurance companies can be performed using different data mining algorithms. The obtained results show that key internal factors for the financial stability of insurance companies change under different economic conditions. During the period of the financial crisis the greatest impact on the financial stability of insurance companies had the quality of management, but also the earning capacity and profitability and liquidity of insurance companies. The classification of insurance companies according to their performance is compared with the official rankings offered by the supervisory body based on the value of the balance sheet assets and the value of premiums paid. It can be concluded that the largest insurance companies are not the most successful in all economic conditions. Inadequate capital management, as well as the inability to generate insurance and investment portfolios, has led to a drastic decrease in the profitability of these insurance companies
Keywords: insurance, financial stability, CARMEL, principal component analysis, cluster analysis